A potential role for neuronal connexin 36 in the pathogenesis of amyotrophic lateral sclerosis - Belousov, Andrei B.; Nishimune, Hiroshi; Denisova, Janna V.; Fontes, Joseph D. (Neuroscience letters, 2018)
•A role for neuronal connexin 36 in the pathogenesis of ALS is proposed.•The mechanism relies on contribution of connexin 36 to ALS-related neuronal death.•A perspective for the use of connexin 36 blockade for ALS therapy is discussed. Neuronal gap junctional protein connexin 36 (Cx36) contributes to neuronal death following a range of acute brain insults such as ischemia, traumatic brain injury and epilepsy. Whether Cx36 contributes to neuronal death and pathological outcomes in chronic neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS), is not known. We show here that the expression of Cx36 is significantly decreased in lumbar segments of the spinal cord of both human ALS subjects and SOD1G93A mice as compared to healthy human and wild-type mouse controls, respectively. In purified neuronal cultures prepared from the spinal cord of wild-type mice, knockdown of Cx36 reduces neuronal death caused by overexpression of the mutant human SOD1-G93A protein. Taken together, these data suggest a possible contribution of Cx36 to ALS pathogenesis. A perspective for the use of blockers of Cx36 gap junction channels for ALS therapy is discussed.